1996
DOI: 10.1002/j.2161-0045.1996.tb00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognitive Theory and the Career Development of African American Women

Abstract: No comprehensive model of the career development of racial and ethnic minorities has yet been developed; even less attention has been devoted to models of the career development of racial and ethnic minority women. One of the more promising career theories that may prove satisfactory in accounting for ethnicity in career development is Bandura's (1986) social cognitive theory (Lent & Brown, 1996; Lent, Brown, & Hackett, 1994). In this article, the authors selectively review the literature on African American w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
248
2
14

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(278 citation statements)
references
References 28 publications
11
248
2
14
Order By: Relevance
“…In particular, our finding showed that career self-efficacy and career interest had strong correlations with large effects for most groups. This result is consistent with the findings of previous research showing that self-efficacy plays a role in career development in Social cognitive career theory (SCCT) (Hackett & Bryars, 1996). Thus, educational strategies that can improve students' self-efficacy about a STEM career could be effective for both Korean and Indonesian students' STEM career development.…”
Section: Relationships Between Each Construct Of Stem Career Motivationsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, our finding showed that career self-efficacy and career interest had strong correlations with large effects for most groups. This result is consistent with the findings of previous research showing that self-efficacy plays a role in career development in Social cognitive career theory (SCCT) (Hackett & Bryars, 1996). Thus, educational strategies that can improve students' self-efficacy about a STEM career could be effective for both Korean and Indonesian students' STEM career development.…”
Section: Relationships Between Each Construct Of Stem Career Motivationsupporting
confidence: 91%
“…In particular, it has been reported that the underrepresentation of women in STEM is closely related to their low self-efficacy in math and science subjects (Hackett & Betz, 1989). In addition, Hackett & Bryars (1996) found that students' belief in whether they have appropriate capacities for a STEM career is an important factor in career development. Thus, career self-efficacy, belief in oneself related to career decisions, goals, and career behavior, was also considered to be a cognitive factor of career motivation in this study.…”
Section: Stem Career Motivationmentioning
confidence: 99%
“…The concept of self-efficacy for youth with disabilities has been studied in a number of venues. For example, research has shown that having previous vocational experience is related to higher levels of self-efficacy (Benz & Halpern, 1993;Hackett & Bryars, 1996;Wehmeyer, 1999). In addition, involvement in the transition process (for example being involved in IEP meetings) has been shown to increase the self-efficacy of youth with some disabilities (Wehmeyer & Lawrence, 1995).…”
Section: Self-efficacy the Concept Of Self-efficacy Is The Theory Thmentioning
confidence: 99%
“…SCCT has been utilized to describe and assess the career development of members of marginalized groups, and has been found to be empirically supported with diverse populations (Chartrand & Rose, 1996;Chronister & McWhirter, 2003;Hackett & Byars, 1996;Morrow, Gore, & Campbell, 1996). SCCT's attention to environmental factors (e.g., poverty, oppression, discrimination), and interactions among the characteristics of the individual and his/her multiple environmental contexts, situate the theory as an ideal theoretical foundation for developing a job-preparation intervention for prerelease inmates.…”
Section: Social Cognitive Career Theorymentioning
confidence: 99%